Self Harm Behavior in 4th Grade Students - Setra Amelia Hutami; Cucu Rokayah; Metty Widiastuti (GLOBAL HEALTH SCIENCE GROUP, 2020)
Self-harm behavior is a form of behavior which someone love to hurt themselves to express the feeling or emotion caused by the mental illness which is felt by the subject. The emotion is hard to be spoken because the problems are too complex, complicated, or full of painful memories or uncontrollable situations. The problems made the subject hurt themselves only to the extent of self-injury and not to the point of committing suicide, however this behavior endangers the doer. The purpose of this study is to discover self-harm behavior which is done by 4th year students of STIKes Dharma Husada Bandung class of 2016. This study employs descriptive method to get the representation of self-harm behavior on 4th year students of STIKes Dharma Husada Bandung class of 2016. The data collection technique used in this study is total sampling with 118 respondents, in which the primary data is collected by means of questionnaire. The analysis literature review shows the result from 118 respondents that 49,2% of the respondents do self-harm behavior with 13,6% caused by sadness, and 10,2% caused by stress. The final result of this study could become the material to evaluate the awareness of 4th year students.